Relevansi Bukti vs Probative Value: Sebuah Dilema dalam Hukum Pembuktian - Zul Khaidir Kadir (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Probative value refers to the extent to which the evidence provided is able to prove the facts being disputed. Evidence may be relevant in the sense that it relates to the case at hand, but relevance alone does not guarantee that the evidence will be well received or considered to have a significant influence. This study uses a qualitative research method with a conceptual approach. The data collection method was collected using library research, then analyzed using qualitative methods and presented descriptively. The results of the study show that the process of proof in criminal law plays a central role in upholding substantive justice. Evidence not only functions as a mechanism to test the truth of claims or accusations brought in court, but also as a tool to protect the human rights of the accused by ensuring that everyone is considered innocent until proven otherwise. Failure to assess probative value can lead to serious injustice in the form of wrongful conviction or wrongful acquittal. To address this problem, it is necessary to increase technical literacy among legal practitioners, as well as the application of more careful procedures in testing the validity and reliability of evidence.